Using patient feedback to adapt intervention materials based on acceptance and commitment therapy for people receiving renal dialysis - James Elander (BMC, 2021)
Abstract Background Theory-based intervention materials must be carefully adapted to meet the needs of users with specific physical conditions. Acceptance and Commitment Therapy (ACT) has been adapted successfully for cancer, chronic pain, diabetes, irritable bowel syndrome, multiple sclerosis, and a range of other conditions, but not so far for people receiving renal haemodialysis. This paper presents findings from a study to adapt ACT-based intervention materials specifically for renal dialysis. Methods Draft written materials consisting of four stories depicting fictitious individuals who used ACT-related techniques to help overcome different challenges and difficulties related to dialysis were adapted using a systematic patient consultation process. The participants were 18 people aged 19–80 years, with chronic kidney disease and receiving renal dialysis. Individual, semi-structured interviews were conducted to elicit participants’ views about how the content of the draft materials should be adapted to make them more realistic and relevant for people receiving renal dialysis and about how the materials should be presented and delivered to people receiving renal dialysis. The interview transcripts were analysed using a qualitative adaptation of the Delphi method in which themes are used as a framework for translating feedback into proposals for modifications. Results The analysis of patient feedback supported the use of patient stories but suggested they should be presented by video and narrated by real dialysis patients. They also indicated specific adaptations to make the stories more credible and realistic. Participant feedback was translated into proposals for change that were considered along with clinical, ethical and theoretical factors. The outcome was a design for a video-based intervention that separated the stories about individuals from the explanations of the specific ACT techniques and provided greater structure, with material organised into smaller chunks. This intervention is adapted specifically for people receiving renal dialysis while retaining the distinctive theoretical principles of ACT. Conclusions The study shows the value of consulting patients in the development of intervention materials and illustrates a process for integrating patient feedback with theoretical, clinical and practical considerations in intervention design.